Express
the Tangent of A in terms of the Cosine of A.

Use
the trigonometric identities to convert between trigonometric functions.

Tangent
A =

Sine A

Tangent
A = ----------

Cosine A

but since sine A ^{ }= Square root of (1 - Cosine^{2 }A),
which can also be written as (1 - Cosine^{2 }A)^{1/2} we get

(1 - Cosine^{2 }A)^{1/2}

Tangent
A = ----------------

Cosine A

This
can be useful if for some reason you have a cosine table but do not have a tangent
table. You can then determine the value
of the tangent even without the tangent table.

The
trigonometric identities used above are as follows:

Sine A

Tangent
A = (Sine A)/(Cosine A)=----------

Cosine A

Sine^{2}
+ Cosine^{2} = 1